2022
DOI: 10.1186/s13046-022-02530-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual epigenetic approach targeting BET proteins and HDACs in Group 3 (MYC-driven) Medulloblastoma

Abstract: Background Medulloblastoma (MB) patients with MYC oncogene amplification or overexpression exhibit extremely poor clinical outcomes and respond poorly to current therapies. Epigenetic deregulation is very common in MYC-driven MB. The bromodomain extra-terminal (BET) proteins and histone deacetylases (HDACs) are epigenetic regulators of MYC transcription and its associated tumorigenic programs. This study aimed to investigate the therapeutic potential of inhibiting the BET proteins and HDACs tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Recent studies have provided mechanistic and pre-clinical evidence for the combination of HDAC inhibitors (HDACi) with BETi, even leading to the development of dual inhibitors. 54 , 55 , 56 , 57 Herein, our combination drug screen revealed that HDACi Panobinostat mostly antagonizes with all tested BETi in the murine GL261 cell line. While these unexpected results were confirmed in the GL261 spheroid model using Panobinostat and Birabresib, a synergistic effect was observed with the same drug combination in the U87 spheroid model.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have provided mechanistic and pre-clinical evidence for the combination of HDAC inhibitors (HDACi) with BETi, even leading to the development of dual inhibitors. 54 , 55 , 56 , 57 Herein, our combination drug screen revealed that HDACi Panobinostat mostly antagonizes with all tested BETi in the murine GL261 cell line. While these unexpected results were confirmed in the GL261 spheroid model using Panobinostat and Birabresib, a synergistic effect was observed with the same drug combination in the U87 spheroid model.…”
Section: Discussionmentioning
confidence: 88%
“…A combination of inhibitors targeting epigenetic regulators histone deacetylase (HDAC) and BET exerted synergistic antitumoral effects in pancreatic cancer (He et al, 2020), glioblastoma (Gusyatiner et al, 2021), and medulloblastoma (Kling et al, 2022). In SCLC xenograft mice, JQ1 and the histone deacetylase 6 (HDAC6) inhibitor ACY-1215 combined to exert antitumor activity dependent on the presence of NK cells (Liu et al, 2018).…”
Section: Combination Therapymentioning
confidence: 99%
“…It important to note that the use of combination therapies has also emerged as an appealing route in the fight against group 3 medulloblastoma due to the aggressiveness and resistance of this subgroup. For instance, it has been shown that the combination of JQ1 with a CDK2 inhibitor (Milciclib), an mTOR inhibitor (BEZ235), or a pan-HDAC inhibitor (Panobinostat) resulted in synergistic anti-cancer effects in MYC-driven group 3 medulloblastoma and amplified the potential of each of the combined agents [131][132][133]. The activity of the pathway is dependent on the Gamma secretase cleavage of the NOTCH receptor, which results in the dissociation of NICD.…”
Section: Group 3 Medulloblastomamentioning
confidence: 99%